(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Social networking marketing is the latest mantra for many brands after early last year. Marketers are seeing the different possibilities in social networking and are starting to introduce innovative social campaigns more quickly than ever before. Social networking ads and the companies that use it have become more advanced Global corporations also recognized social media marketing as a possible marketing tool, used them with inventions to fuel their promotional strategy with social media marketing. This paper discusses about the concepts of social marketing and social media marketing and Components of social Marketing’s ‘4ps’, Social Media Marketing in India, Concepts in Social Marketing Theory, and Major Features of Social Marketing Theory ,Forms of social marketing ,Use of Social Media Marketing.